Underestimation of Leptospirosis Incidence in the French West Indies. - Sylvie Cassadou; Jacques Rosine; Claude Flamand; Martina Escher; Martine Ledrans; Pascale Bourhy; Mathieu Picardeau; Philippe Quénel (Public Library of Science (PLoS), 2016)
BACKGROUND:Leptospirosis is a neglected zoonosis affecting mainly tropical and subtropical regions worldwide, particularly South America and the Caribbean. As in many other countries, under-reporting of cases was suspected in the French West Indies because of inadequate access to diagnostic tests for the general population. METHODOLOGY/PRINCIPAL FINDINGS:In order to estimate the real incidence of leptospirosis in Guadeloupe and Martinique, a study was performed in 2011 using the three prevailing available biological tests for diagnosis: Microscopic Agglutination Test (MAT), IgM ELISA and PCR. The study investigated inpatients and outpatients and used active case ascertainment from data provided by a general practitioners' sentinel network. The epidemiology of the disease was also described in terms of severity and demographic characteristics. Leptospirosis incidence was estimated at 69.4 (95%CI 47.6-91.1) and 60.6 (95%CI 36.3-85.0) annual cases per 100,000 inhabitants in Guadeloupe and Martinique, respectively, which was 3 and 4 times higher than previous estimations. CONCLUSION/SIGNIFICANCE:Inclusion of PCR and IgM ELISA tests for diagnosis of leptospirosis resulted in improved sensitivity in comparison with MAT alone. Our results highlighted the substantial health burden of the disease in these two territories and the importance of access to appropriate laboratory tests. Based on our results, PCR and IgM ELISA tests have now been included in the list of tests reimbursed by the national system of social security insurance in France. Our results also underline the relevance of implementing an integrated strategy for the surveillance, prevention and control of leptospirosis in the French West Indies.